Analysis Of Shells and Folded Plate Structures By Finite Element Method - Bhat, M. S. (My University, 1969)
A computer program is written to calculate the deflections and stresses in a shell of general nature.
An oblique. truncated pyramid, built of aluminium plates is used for illustration and experimental analysis.
Theoretical values of deflections and stresses are compared with the experimental results.
Keywords: plate structure; finite element method; shell deflections; shell stresses